2022
DOI: 10.1016/j.ajo.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Career Decisions and Satisfaction Among Newly Practicing Ophthalmologists

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 276 publications
(454 reference statements)
0
6
0
Order By: Relevance
“…Academic medicine provides opportunities for research, care of patients with complex medical problems, and education of physicians-in-training. Despite these attractions, there have been growing concerns about a perceived diminished workforce in academic medicine, including ophthalmology . Therefore, it is particularly important to understand factors that predict this career pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Academic medicine provides opportunities for research, care of patients with complex medical problems, and education of physicians-in-training. Despite these attractions, there have been growing concerns about a perceived diminished workforce in academic medicine, including ophthalmology . Therefore, it is particularly important to understand factors that predict this career pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Increasing emphasis on career advancement and wellness aligns with growing interests in optimizing personal performance among ophthalmologists. 38 39 Podcasts, therefore, may help openly disseminate the kind of advice typically gleaned from a mentor-mentee relationship. It is also apt that the digital modality of podcasts promoted digital technology education.…”
Section: Discussionmentioning
confidence: 99%
“… 5 10 Prior studies have found that gender modulates both intent to pursue subspecialty training and pursuit of specific subspecialties within ophthalmology; however, such an analysis was not within the scope of our present study. 11 12 In addition, a previous study examining retention within plastic surgery demonstrated that recent graduates may be less likely to be internal hires compared to faculty who did not graduate as recently. 3 In our study, we found that, on the contrary, fewer years since completion of residency was a significant predictor of internal hiring.…”
Section: Discussionmentioning
confidence: 99%